Pesantren Persatuan Islam dan Kontribusinya bagi Perkembangan Pemikiran di Indonesia - Kusdiana, Ading (UIN Sunan Gunung Djati Bandung, 2023)
This article aims to find out about the existence of the Islamic Association Islamic Boarding School (Persis) and its contribution to the development of thought in Indonesia. From the research results, it can be revealed that the existence of the Islamic Unity Islamic Boarding School which is widely spread in various regions in Indonesia cannot be separated from the establishment of the Pajagalan Islamic Unity Islamic Boarding School as the first Islamic Unity Islamic Boarding School which was founded in 1936. To date, the Islamic Unity Islamic Boarding School has made many contributions in encouraging the Islamic renewal movement, instilling a sense of nationality, supporting the founding of the Republic of Indonesia, participating in defending the independence of the Republic of Indonesia and rejecting communist ideology, as well as maintaining unity and revitalizing the dynamics of religious life.